1999
DOI: 10.2139/ssrn.170009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Race in School Finance Reform

Abstract: Magill for their helpful comments on earlier drafts. Toby Heytens, Mary Kane, and Sue Messenger provided terrific research assistance; a special thanks to Darcy Goddard for her indefatigable research and editorial assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Attempting to gain more funding for African American students from the state is problematic as Ryan (1999) found. His study indicated that poor districts with predominately minorities residing therein, fail to convince lawmakers and even the courts for greater financial resources.…”
Section: More Funding Neededmentioning
confidence: 99%
“…Attempting to gain more funding for African American students from the state is problematic as Ryan (1999) found. His study indicated that poor districts with predominately minorities residing therein, fail to convince lawmakers and even the courts for greater financial resources.…”
Section: More Funding Neededmentioning
confidence: 99%
“…Where racial segregation exists, opportunities and life chances for individuals in the racial/ ethnic groups involved tend to be fundamentally unequal (Kozol, 1991(Kozol, , 2006Gaskin et al, 2012). The tradition of local control of public education in the United States entails that schools located in predominantly white and often affluent neighborhoods tend to have greater and higher quality resources than those located in predominantly minority neighborhoods (Kozol, 1991(Kozol, , 2006(Kozol, , 2012Ryan, 1999). More white and affluent communities have a higher tax base, and this enables them to afford better funding for schools, which can be seen in up-to-date textbooks, better paid teachers, smaller class sizes, and an overall physical environment that fosters learning (Kozol, 2006(Kozol, , 2012Ryan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The tradition of local control of public education in the United States entails that schools located in predominantly white and often affluent neighborhoods tend to have greater and higher quality resources than those located in predominantly minority neighborhoods (Kozol, 1991(Kozol, , 2006(Kozol, , 2012Ryan, 1999). More white and affluent communities have a higher tax base, and this enables them to afford better funding for schools, which can be seen in up-to-date textbooks, better paid teachers, smaller class sizes, and an overall physical environment that fosters learning (Kozol, 2006(Kozol, , 2012Ryan, 1999). Schools in less affluent neighborhoods, on the other hand, tend to have out-of-date textbooks, less paid teachers, beginning and less prepared teachers, larger class sizes, crumbling infrastructure, and low teacher expectations (Gregory et al, 2010;Hanushek & Rivkin, 2009;Kozol, 1991).…”
Section: Introductionmentioning
confidence: 99%